The show makers : great directors of the American musical theatre - Thelen, Lawrence (Routledge, 2000)
The Show Makers describes twelve of the most creative and influential directors of contemporary musical theatre. Richly anecdotal, The Show Makers communicates the passion and joy which motivates these directors.